Life Skills Education Through Non-Formal Education For People With Physical Disabilities - Mahfuzi Irwan; Aisyah Anggreni; Jihan Sunita; Herman Suhdi (Universitas Negeri Padang, 2022)
This study aims to identify and identify life skills education through non-formal education for persons with physical disabilities. Individuals who have physical limitations are called persons with physical disabilities. In the social environment, society tends to give negative stigma to people with physical disabilities and other problems that are in the spotlight are the low participation and provision of job opportunities for people with disabilities in obtaining work. This study used qualitative research methods. This research is sourced from secondary data obtained from documents, journals related and in line with physical disabilities and life skills education for physical disabilities. The result of this literature review is that empowerment of disabled groups must be carried out to increase participation in various fields of social life with adequate and relevant work skills. Skill enhancement is provided to gain accessibility for persons with disabilities, one of which is through non-formal education programs, namely life skills education. Vocational rehabilitation as a form of life skills education through non-formal education is carried out by providing services in the form of skills training activities that aim to cultivate, develop and increase the potential possessed by persons with disabilities, especially persons with physical disabilities.